Hubungan Student Engagement dengan Perilaku Cyberslacking Melihat Peran Mediasi Academic Boredom pada Mahasiswa Gen Z - Vionita Felicia Nugraha Purnomo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the relationship between student engagement and cyberslacking behavior by considering the mediating role of academic boredom among Gen Z university students. As digital technologies become increasingly embedded in learning environments, understanding how psychological factors influence students’ online distractions is essential. Using a quantitative approach and path analysis, the findings show that student engagement significantly reduces academic boredom, while academic boredom significantly increases cyberslacking behavior. Furthermore, student engagement directly and indirectly influences cyberslacking, with academic boredom acting as a partial mediator. These results highlight that low engagement does not only predict higher disengagement behaviors but also triggers psychological states specifically academic boredom that drive students to divert attention to non-academic digital activities during class. This study demonstrates that cyberslacking is not merely a technological issue but also a reflection of the internal learning experiences of Gen Z students. The implications emphasize the need for learning designs that are interactive, meaningful, and capable of sustaining engagement to minimize digital distractions.